Family and marriage social institution in young people’s minds and its support in modern Russia - T. E. Petrova; Z. V. Zhiratkova; A. G. Kovalchuk (Цифровая социология, 2025)
The evolution of perception and meaning of family and marriage for society as a whole and for young generation in a rapidly changing social and cultural context has been studied. It has been noted that the role of social, cultural, and religious factors changes in different epochs. The impact of globalization, rapid technological development, and changing social norms on traditional ideas about family and marriage has been considered. The authors undertook an online research of value preferences of student youth in Moscow, Penza, Saransk, Tver, Ufa, and Kazan universities (a total of 738 people were interviewed) and identified the most stable priorities, including family, health, education, and work. The normative base of Russian family policy has been analyzed, including the national development goals of Russia (demographic growth, population conservation, and traditional values protection). The current demographic situation in modern Russia has been characterized. It has been revealed that the most important component of traditional spiritual values is family values. The most urgent in the modern historical situation are the issues of strengthening the family and marriage institution, popularization among the younger generation of traditional family values, chastity, and healthy lifestyle as the basis of family well-being, enrichment of positive social and cultural experience of students on the basis of education in the spirit of traditional Russian moral values, compliance with the rules and behavioral norms accepted in society, social and family traditions maintenance. Changes in emotional and practical aspects of relationships, the role of traditional values and modern trends, such as the desire for individualism and alternative forms of family life, the transition from patriarchal to more equal models of family relations have been analyzed. The spread of alternative forms of kinship relations (cohabitation, same-sex marriages, and cohabitation without official registration) has been revealed. Federal and regional measures to support families, including young families, have been characterized. The study emphasizes the importance of understanding these changes for sociologists, psychologists, and practitioners working with youth.